VARIOUS AND INTENCITY PARASITIC INFECTIONS IN CATTLE FARMER GROUP NITI SARI IN BATURITI VILLAGE, TABANAN REGENCY - Apsari, Ida Ayu Pasti; Kencana, Gusti Agung Ayu Yuniati; Mahardika, Gusti Ngurah Kade; Astawa, Nyoman Mantik; Kendran, Anak Agung Sagung; Suartha, I Nyoman; Widyastuti, Srikayati; Suardana, Ida Bagus Kade; Dewi, I Gusti Ayu Mayani Kristina; Sudiarta, I Putu (Buletin Veteriner Udayana, 2022)
Parasitic infections are inseparable from the epidemiological triangle, namely host, agent and environment. Bali cattle as host of parasitic agents are affected by infection by environmental conditions in the village of Baturiti. The purpose of this study was to determine the prevalence and  intensity of parasitic infections in cattle from the Niti sari farmer group in Baturiti village. A total of 55 Bali cattle in Niti Sari farmer group cattle were used as samples. Stool samples are taken to check for the presence of parasites and predict the amount of parasitic  load  that  infects. The method of checking the presence of parasites by floatation test and prediction of parasitic load by the Stool method. The results obtained were the prevalence of Coccidia protozoa 52.73% (29/55), Entamoeba sp.16.36% (9/55), Balantidium  sp.20.9% (6/55) with intensity of infection  respectively 1255.17 ± 964.82 oocysts/gram,  233.3 ± 250 cysts /gram and 150 ± 83.67 cysts/gram feces. The prevalence of Strongyl worm eggs is 61.82% (34/55), Strongyloides sp. 23.64% (13/55) and Toxocara sp. 18.18% with an infection intensity respectively of 420.59 ± 233.26 eggs/gram, 253.85 ± 64.55 eggs/gram and 130 ± 48.3 eggs / gram. Conclusion of Bali cattle in the farmer group Niti Sari Baturiti village infected with the parasitic protozoa Coccidia, Entamoeba sp and Balantidium sp. with low to moderate intensity. Infection by Strongyl, Strongyloides sp. and Toxocara  sp. nematodes with low intensity.